Future Teachers Forming Professional Expectations in Modern Educational Conditions - Yudina, Irina Aleksandrovna (2020)
The relevance of the present study lies in improving the training of future teachers, an issue of particular importance during a pandemic. The authors aim to identify the level of professional expectations of future teachers and determine the necessary conditions for them to be upgraded. Study objective: The study was focused on evaluating the level of professional expectations of future teachers (PEFT) and revealing conditions catering for its improvement. Methodology: Both theoretical and empirical methods were used in the study: based on literature review the authors compiled PEFT components (motivational, emotional, cognitive, and value-semantic) and the substantial characteristics of these components were listed. In accordance with the selected components, a questionnaire was designed to identify the actual level of professional expectations among students. The experiment results were analyzed both qualitatively and quantitatively. Experiment results: The study reveals the role of professional expectations in raising the efficiency of teachers’ professional activities. PEFT components and substantial features have been established. Recommendations are provided to elicit positive PEFT formation using the University educational environment.  The practical implications of the study: The nuances of professional expectations development among future teachers have been identified. When organizing professional education, these nuances should be considered for increased effectiveness and for greater success of graduates in their professional activities.